Bibliometrik Menggunakan Vosviewer dengan Publish or Perish: Penelitian Neural Network dalam Klasifikasi Penyakit Tanaman - Nova Rahma; Imamatul Khoiriyah; Suhartono (Jurnal Informatika dan Sains Media (JISMA), 2024)
Plant diseases pose a severe threat to global food security and agricultural sustainability. The impact of plant diseases causes economic losses for farmers and food shortages for the population. To overcome this problem, research in agriculture utilizes advanced technologies such as neural networks to detect plant diseases. This study aims to understand the development of research on using neural networks in plant disease classification. This method used the Neural Network method to identify plant diseases from images, with a bibliometric analysis of 72 articles published between 2019 and 2024. The results of this study map the network of knowledge and collaboration in the use of neural networks for plant disease classification, identifying three main clusters that reflect the research focus and application of this technology. It was concluded that this study successfully understood the research developments related to using neural networks in plant disease classification.